Analysis of Communication Barriers In The Implementation Of Universal Service Obligation (USO) Programme In Indonesia: A Literature Study - Ayuni, Qurata; Yualifah; Kalalembang, Erik; Arsyad, Emil (International Journal of Global Community, 2018)
This study is designed to explain the communication barriers affecting internal and external information flow in the implementation of the universal service obligation (USO) programme in many different areas of Indonesia. An Analysis of relevant literature will result in a comprehensive classification. There are serious horizontal and vertical communication obstacles between the central government, local government, equipment and service provider, communication and technology network provider, village apparatus as well as the society due to lack of socialisation, coordination and written rule as implementation guidance of the USO programme. Due to the existence of communication barriers, the Information and Communication Ministry and other stakeholders should form a strategic path and proffer solutions to effectively address the problems that could negatively influence the progress of the programme by efficient use of the USO budget.